Research on the influence of the morphology of coarse aggregates from Reclaimed Asphalt Pavement (RAP) on the mechanical properties of asphalt concrete based on finite element modeling - Nan Ru; Yu Zhao; Zhaoting Liu; Ya Li; Shuangchen Xia; Wencheng Cheng (PLoS ONE, 2025)
Using recycled coarse aggregates (RCA) to prepare asphalt mixtures can reduce the consumption of natural sand and gravel resources and solve the environmental pollution problem caused by waste asphalt concrete materials. To promote the widespread application of RCA, research has been conducted on fully recycled asphalt concrete (FRCAC). The ABAQUS finite – element software was used, and a random aggregate placement algorithm for RCA was implemented by writing the built – in scripting language Python to generate digital specimens. After obtaining the material parameters through indoor tests, the digital specimens were analyzed. Four aggregate characteristic parameters, namely aspect ratio, shape parameter, roundness ratio, and angularity, were selected to further describe the relationship between the external features of RCA and the mechanical properties of asphalt concrete. The results show that: (1) As the irregularity of the RCA’s external shape increases, the ultimate failure load of the specimens shows an upward trend. (2) When the aspect ratio reaches 1.70 to 1.75, the shape parameter reaches 0.70 to 0.75, the roundness ratio is between 0.84 to 0.82, and the angularity reaches 0.76 to 0.74, the ultimate failure load of the specimens shows a downward trend. (3) The finite-element modeling algorithm can well reflect the morphology of coarse aggregates and accurately characterize the influence of aggregate morphology on the mechanical properties of asphalt mixtures.